Exploring genebank for identification of biotic–abiotic combined tolerance in wild Phaseolus - Mosquera Cifuentes, Gloria Maria; Cotes, Carlos; Arredondo, Victoria; Beebe, Stephen E.; Barrera, Santos (2018)
Climate change is an important factor that is impacting production and distribution of beans, affecting directly plant development and indirectly by influencing changes in disease patterns. By 2020, an increase in precipitation would be expected in many African countries, and under these conditions root rot diseases will be favored. In order to address these limitations, it is necessary to find new genetic variants that could be used by breeding programs to develop better varieties resilient to climate change. Wild bean relatives are a useful resource that must be explored more extensively, since they harbor genes important for bean adaptation to diverse environments, and can be used to improve cultivated beans with superior performance against abiotic and biotic stress. More than 150 accessions from including Phaseolus vulgaris, Phaseolus coccineus, Phaseolus dumosus, Phaseolus costaricensis and Phaseolus albescens were phenotyped under greenhouse conditions for waterlogging tolerance and Pythium myriotylum resistance.